2019
DOI: 10.1002/ijfe.1731
|View full text |Cite
|
Sign up to set email alerts
|

Customer concentration, institutions, and corporate bond contracts

Abstract: We examine the effect of customer concentration, the quality of institutions, and their interaction on corporate bond contract terms in China. We find that higher customer concentration is associated with higher bond spreads, shorter bond maturity, and more bond covenants. In contrast, better institutions are associated with lower bond spreads, longer bond maturity, and fewer bond covenants. Moreover, we find that the adverse or unfavourable association between customer concentration and bond contract terms is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
0
14
1
Order By: Relevance
“…Following the literature (e.g., Peng et al, 2019;Liu et al, 2020), this study uses the firm's sales to the top 5 customers divided by total sales to measure customer concentration. Following Baron and Kenny (1986), this study constructs the model as follows:…”
Section: Regression Model For Customer Concentration's Moderating Effectmentioning
confidence: 99%
“…Following the literature (e.g., Peng et al, 2019;Liu et al, 2020), this study uses the firm's sales to the top 5 customers divided by total sales to measure customer concentration. Following Baron and Kenny (1986), this study constructs the model as follows:…”
Section: Regression Model For Customer Concentration's Moderating Effectmentioning
confidence: 99%
“…PSM has been described as the most developed and popular approach for processing data to improve causal inference in observational studies (Pearl, 2010). The main advantage of PSM in our context is that it does not rely on classical regression assumptions such as linear functional form or serially non-correlated errors, and can satisfactorily deal with the endogeneity problem (Cushman & De Vita, 2017;Liu, Xiao, & Xie, 2019). The latter virtue could be particularly advantageous in application to the present study given that legal origin is a variable that is constant at the country level and there may be many other country-level factors correlated to it, so it is impossible to isolate the effect of legal origin from the effect of other country-wide institutions.…”
Section: Highlightsmentioning
confidence: 99%
“…Many domestic and foreign scholars have done research with customer concentration as the starting point. The vast majority of literature found that the higher the customer concentration, the higher the business risks facing the company [28,[41][42][43]. The over-reliance on large customers means such companies' financial strategies tend to be conservative, with less innovation and R&D. However, some studies are based on specific environmental systems, with large customers considered to be beneficial to promote supply chain integration and reduce corporate risk [26], and enabling them to invest more resources in their development process.…”
Section: The Influence Mechanism Of Government Clients On Innovation mentioning
confidence: 99%